Experimental and numerical study of effective thermal conductivity of cracked concrete. (30th October 2017) - Shen, Lei; Ren, Qingwen; Zhang, Linfei; Han, Yan; Cusatis, Gianluca
Highlights: Simulations show concrete thermal conductivity has a decrease of 20–30% during tensile and compressive failure. Debonding of aggregate and mortar dominants the reduction of concrete thermal conductivity. Experiments show a 25% decrease in thermal conductivity during compressive test. Wang Jiajun model is calibrated to calculate the thermal conductivity of cracked concrete. Abstract: The pronounced decrease of Effective Thermal Conductivity (ETC) due to the cracking behavior of concrete changes the temperature profile in concrete structures, indirectly inducing the redistribution of thermal stresses. To study this phenomenon, a mini-scale numerical method within the framework of finite element method is proposed for both tensile and compressive cracked concrete and this method is applied to obtain quantitative relationships between tensile or compressive strain and ETC. Results show that (a) for tensile dominated failure, concrete ETC decreases by 23% during the plastic stage whereas little decrease is found at complete failure; (b) for compressive dominated failure, ETC decreases by 30% during the plastic stage, and then becomes stable afterwards. In the softening stage ETC linearly decreases with the increase of compressive strain; (c) it is the interfacial thermal resistances induced by the micro-cracks between aggregates and mortar rather than the macro-cracks that play the dominant role in this phenomenon; (d) concrete ETC becomes anisotropic when cracks appear. The experiments show that compressive cracked concrete's ETC vertical to cracks dramatically decreases by 20–25% at plastic drop stage and then becomes stable at the plastic steady stage. The numerical results are used to determine the interfacial thermal resistance factor in Wang Jiajun model. The proposed formulation provides results that are in excellent agreement with experiments.